An Examination Some of Educational – Extension Factors Influencing Use of Transgenic Plants (Case Study: Ilam, Iran) - Mohammad Bagher Arayesh (International Journal of Agricultural Management and Development, 2015)
The purpose of this study was to examine the effect of educational – extension factors on the use of transgenic plants. This study was conducted through a survey design. The research was an applied study type. The research method of this study is descriptive-correlation. Statistical population of the study consisted of all of biotechnology experts of Research Center of Agriculture of Ilam Province (N=63). Census method was used in this study. A questionnaire was the main tool which the face and content its validity was confirmed by panel of University Experts. Reliability Coefficient (Cronbach's alpha) of the questionnaire was 92%. Results showed that the use of media (radio and TV) was the most important factor in the use of transgenic plants. The result of Spearman correlation coefficients showed that, there was a significant relationship between the variables such as the use of communication media, communication with extension professionals, and scientific rank of professional with use of transgenic plants. Multiple regression analysis results showed that varriables like scientific rank, relationship with extension professionals and mass media have positive effect on the dependent variable of application of transgenic plants, describing 53.2% of the changes of the mentioned dependent variable.